Recherches sur Jean Grolier, sur sa vie et sa bibliothèque, suivies d'un Catalogue des livres qui lui ont appartenus - Lincy, Antoine-Jean-Victor le Roux de (European History and Culture - Book Archive pre-2000., 1970)
The Catalogue (pp. 179-320), extensively describing 349 items ( 13 of which are manuscripts) gives a masterly reconstruction of Grolier's Library, which ranks among the most precious collections of books of all times. The owner (1479-1565) is rightly considered as the founding father of French bibliography.